2008
DOI: 10.1186/1748-717x-3-29
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT imaging for staging and radiotherapy treatment planning of head and neck carcinoma

Abstract: PET/CT fusion images could have a potential impact on both tumor staging and treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…al. it was stated that TNM stage and clinical stage were altered with the PET/CT in 22 % of the cases (Deantonio et al, 2008). Connel et.…”
Section: Discussionmentioning
confidence: 99%
“…al. it was stated that TNM stage and clinical stage were altered with the PET/CT in 22 % of the cases (Deantonio et al, 2008). Connel et.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was difficult to identify musculature, major vessels including the carotid artery and jugular vein, and maxillary sinuses, which were readily delineated in the same subjects with the use of CT and MRI. The utility of FDG-PET/CT for diagnosing head and neck cancers has been reported, and it was found that the method shows both anatomical and functional images simultaneously (15,16). Additional investigations of PET/CT with fluoridelabeled BPA as a tracer are warranted, not only for improving the diagnostic potential, but also for treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…They compared results of conventional diagnostic methods and PET/CT and reported a change in TNM classification in 5 cases. Overall gross tumor volume was higher by 6 cm 3 based on PET/CT, in comparison with CT based GTV [12].…”
Section: Discussionmentioning
confidence: 97%
“…Data from the literature suggests that treatment planning based on PET-CT may considerably differ from the planning based solely on CT imaging [11,12]. Estimated 30% to 40% of radiation plans were modified due to the use of PET examinations in the planning process.…”
mentioning
confidence: 99%